60 Years of Glacier Elevation and Mass Changes in the Maipo River Basin, Central Andes of Chile - Farias-Barahona, David; Ayala, Alvaro; Bravo, Claudio; Vivero, Sebastian; Seehaus, Thorsten; Vijay, Saurabh; Schaefer, Marius; Buglio, Franco; Casassa, Gino; Braun, Matthias H. (My University, 2020)
Glaciers in the central Andes of Chile are fundamental freshwater sources for ecosystems and communities. Overall, glaciers in this region have shown continuous recession and down-wasting, but long-term glacier mass balance studies providing precise estimates of these changes are scarce. Here, we present the first long-term (1955-2013/2015), region-specific glacier elevation and mass change estimates for the Maipo River Basin, from which the densely populated metropolitan region of Chile obtains most of its freshwater supply. We calculated glacier elevation and mass changes using historical topographic maps, Shuttle Radar Topography Mission (SRTM), TerraSAR-X add-on for Digital Elevation Measurements (TanDEM-X), and airborne Light Detection and Ranging (LiDAR) digital elevation models. The results indicated a mean regional glacier mass balance of -0.12 +/- 0.06 m w.e.a(-1), with a total mass loss of 2.43 +/- 0.26 Gt for the Maipo River Basin between 1955-2013. The most negative glacier mass balance was the Olivares sub-basin, with a mean value of -0.29 +/- 0.07 m w.e.a(-1). We observed spatially heterogeneous glacier elevation and mass changes between 1955 and 2000, and more negative values between 2000 and 2013, with an acceleration in ice thinning rates starting in 2010, which coincides with the severe drought. Our results provide key information to improve glaciological and hydrological projections in a region where water resources are under pressure.
Keywords: glacier mass balance; glacier elevation changes; mountain glaciers; central andes; lidar; insar